1990
DOI: 10.1073/pnas.87.15.5868
|View full text |Cite
|
Sign up to set email alerts
|

Brain G protein gamma subunits contain an all-trans-geranylgeranylcysteine methyl ester at their carboxyl termini.

Abstract: We have shown previously that guanine nucleotide-binding protein (G protein) beta gamma complexes purified from bovine brain membranes are methyl esterified on a C-terminal cysteine residue of the gamma polypeptide. In the present study, 3H-methylated G beta gamma complexes cleaved to their constituent amino acids by exhaustive proteolysis were shown to contain radiolabeled material that coeluted with geranylgeranylcysteine methyl ester on reversed-phase HPLC and two TLC systems. Further treatment by performic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
117
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(118 citation statements)
references
References 37 publications
1
117
0
Order By: Relevance
“…First, we examined whether the prenyl moiety that is post-translationally added to the γ subunit is the main determinant of the differential translocation. γ5 is geranylgeranylated and γ11 is farnesylated [17,18]. A farnesylated γ5 subunit mutant translocated more rapidly compared to the wild type γ5 but slower than the γ11 subunit.…”
Section: Introductionmentioning
confidence: 97%
“…First, we examined whether the prenyl moiety that is post-translationally added to the γ subunit is the main determinant of the differential translocation. γ5 is geranylgeranylated and γ11 is farnesylated [17,18]. A farnesylated γ5 subunit mutant translocated more rapidly compared to the wild type γ5 but slower than the γ11 subunit.…”
Section: Introductionmentioning
confidence: 97%
“…Certain other CAAX containing proteins, including the ras-related proteins Krev 1/rap lA (Kawata et al, 1990;Buss et al, 1991) and G25K (Maltese and Sheridan, 1990), and the -y-subunits of brain G-proteins (Yamane et al, 1990;Mumby et al, 1990) have been shown to be geranylgeranylated. The CAAX motifs of these C20 modified proteins all terminate with a leucine residue indicating that the X amino acid determines whether a CAAX motif is a substrate for a farnesyl or geranylgeranyl transferase (Seabra et al, 1991;Finegold et al, 1991).…”
Section: Oxford University Pressmentioning
confidence: 99%
“…Although none of the G-protein subunits contain regions that might obviously associate with a lipid bilayer, the heterotrimer is bound to the plasma membrane due in part to the fact that the 7/-subunits are prenylated [5][6][7][8]. The carboxyl-terminal posttranslational modifications of G-protein 7~-subunits are important determinants of the subcellular location of the G-subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal 71 and brain ;g2 proteins have been shown to contain farnesyl [5,6] and geranylgeranyl [7,8] modifications in the C-terminal cysteine residues, respectively. On the other hand, the G~ proteins of the G i subfamily are myristoylated [9] and members of the Gs and Gq subfamilies of ~ units are palmitoylated [10,11].…”
Section: Introductionmentioning
confidence: 99%